Bid Evaluation and Assessment of Innovation in Road Construction Industry: A Systematic Literature Review - Pardeep Kumar Oad; Stephen Kajewski; Arun Kumar; Bo Xia (Salehan Institute of Higher Education, 2021)
Objectives: This paper present a thorough understanding of bid evaluation process and assessment of innovation in road construction industry. Methods/Analysis: The research articles reviewed are based on topics of bid evaluation process, evaluation of bids in road construction industry, the indicators and techniques of bids evaluation, process of Bid evaluation in countries, innovation in road industry, and indicators of innovation in the context of road construction industry. Findings: It is widely accepted that projects related to the road construction must be accomplished in an organized manner. Literature indicates that the road constructing demands from customers and competition of assessing and evaluating tenders have been increasing rapidly. Novelty /Improvement: Challenges in developing suitable roads contribute to the inconsistency in the industry and directly demands towards physical work on a road construction project, nevertheless, a failure to accurately assessment of tenders can lead to complications for the whole project and road Construction Company. The selection of a suitable construction contractor’s surges likelihoods of successful achievement of a road construction project. This may also achieve the customer goals, and retain the project schedule on time, within the budget and achieve high quality project. Doi: 10.28991/cej-2021-03091646 Full Text: PDF